PREVALENCE AND RISK FACTORS OF PRE-ECLAMPSIA AMONG EXPECTANT MOTHERS: A CROSS-SECTIONAL STUDY AT A HOSPITAL SETTING: JPUMHS;2024:14:04,176-184. http://doi.org/10.46536/jpumhs/2024/14.04.577 - Bushra Noor Khuhro1, Nusrat Fozia Pathan2, Kainat3, Shahzadi Pir4, Rashida Akbar Ghumro5, Areeba Batool6, Aqsa7, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Pre-eclampsia continues to be a leading cause of complications during pregnancy, especially in low- and middle-income regions. OBJECTIVE: This study was conducted to determine how widespread pre-eclampsia is and to identify contributing risk factors among women receiving antenatal care at a tertiary-level hospital. METHOLOGY: Employing a cross-sectional approach, information from 384 participants was gathered via interviews, clinical evaluations, and reviews of patient records. Data analysis was done using SPSS version 26. RESULT: The findings revealed a prevalence rate of 8.7%. Notable associations were identified between pre-eclampsia and factors such as maternal age, parity, BMI, and a personal or family history of hypertension. CONCLUSION: These results highlight the importance of early identification and intervention for at-risk pregnant women to improve maternal and neonatal outcomes.